2002
DOI: 10.1006/viro.2002.1519
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Turnip mosaic virus P3 and Cylindrical Inclusion Proteins Are Separately Required to Overcome Two Brassica napus Resistance Genes

Abstract: The Brassica napus differential line 165 is resistant to infection by Turnip mosaic virus (TuMV) isolates belonging to pathotypes 1 and 3. Nucleotide sequences of resistance-breaking mutants of pathotype 1 (UK 1), pathotype 3 (CHN 12), and wild-type isolates have been determined. When the mutations identified were introduced into an infectious clone of UK 1, a single mutation in the viral P3 protein induced a hypersensitive (necrotic) response in inoculated leaves of line 165 plants. Full systemic nonnecrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 45 publications
5
87
0
2
Order By: Relevance
“…Antagonistic pleiotropy has been shown to explain resistancebreaking-associated fitness costs in several plant viruses (16,17,58,59), as shown here for some interactions. Our results also provide evidence of resistance breaking without cost, as occasionally reported (48,(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Antagonistic pleiotropy has been shown to explain resistancebreaking-associated fitness costs in several plant viruses (16,17,58,59), as shown here for some interactions. Our results also provide evidence of resistance breaking without cost, as occasionally reported (48,(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 56%
“…Evidence for resistance-breaking fitness costs derives mostly from analyses of the multiplication of resistancebreaking and wild-type virus genotypes in a susceptible host genotype. Previous reports refer to different plant-virus systems (16,18,(58)(59)(60), including the pepper-PMMoV system analyzed here (17).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether P3 of SMV is also involved in pathogenicity of the virus in soybean genotypes lacking Rsv1. In the case of the Turnip mosaic virus-Brassica pathosystem, strain-specific P3 of the virus has been identified as the virus elicitor for both TuRB03-and TuRB04-mediated resistance responses, and it has been proposed that it also plays a role in pathogenicity (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the 59-2491 regions did not play a significant role in the differential infection phenotype between TuC and TuR1, suggesting that the central region (positions 2491 to 6130) might affect host-specific infection and symptomatology of TuMV. The central region of potyvirus polyproteins has been reported to affect pathogenicity and symptomatology in specific hosts or one plant species (Chu et al, 1997;Dallot et al, 2001;Hjulsager et al, 2002;Jenner et al, 2000Jenner et al, , 2002Johansen et al, 2001;Sáenz et al, 2000). As expected, the progeny virus 5 caused the same host responses as TuC, and the reciprocal recombinant 6 caused the same host responses as TuR1.…”
Section: Exchanges Of the P3 Genes Alter Infection Phenotype Of Tumvmentioning
confidence: 99%
“…Among potyviruses there is relatively little similarity in P3 proteins compared to other proteins (Urcuqui-Inchima et al, 2001). The P3 proteins are thought to be involved in virus replication (Merits et al, 1999), accumulation (Klein et al, 1994), symptomatology (Chu et al, 1997;Sáenz et al, 2000), resistance breaking (Hjulsager et al, 2002;Jenner et al, 2002Johansen et al, 2001) and cell-to-cell movement (Dallot et al, 2001;Johansen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%